The Indo-European Family Tree and its Split – a Report from the Workshop "The Indo-European Family Tree" - Piotr Garbacz (Ksiegarnia Akademicka Publishing, 2018)
The paper provides an overview of a number of recent presentations of the Indo-European family tree and the split off its branches, as found in standard textbooks on the topic. These views are contrasted against the results of a workshop, The Indo-European family tree (University of Copenhagen, 15–17 Feb. 2017). Our account specifically addresses whether there are reasons to assume the existence of Italo-Celtic, Graeco-Armenian and what is the position of the Germanic branch in the tree. The use of new archaeological methods, computational cladistics and DNA-studies and their possible importance for diachronic linguistics are also mentioned.